Unlocking the Prospects of Disruptive Technology : A Comparative Learning Case - Bhattacharjee, Sandeep (Indian Journal of Computer Science, 2016)
Technology and humans coexist in the modern era. Both are dependent on each other. Human growth and development depends upon the use of better technology. This synergistic relationship has been existing since the dawn of humankind, with the inventionof simple apparatus and continues into modern technologies such as the printing press and computers, laptops, supercomputers and so on. The rate of growth of technology is increasing manifolds. Something surprising today may be a thing of the past in the future. In this research paper, we tried to understand such fast, non-conventional growth of certain raw designs that support out of the box thoughts.